Islamic Philanthropy as an Instrument of Economic Justice - M. Dhaffin Fawwaz Fadiilah (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2026)
Philanthropy is a concept that has been present in Islam, which aims for good (al - birr) , look at the condition of the level of social and economic society different, idea or concept of philanthropy is one alaternatif for a community group to reduce social inequalities among communities. Effectiveness of philanthropy in an effort to reduce social inequalities can not be separated from the role of philanthropic institutions that manage these activities. The potential that comes from this very large philanthropy by implementing capital distribution to those who are unable to, so it can play a role in economic activity, as manufacturers increase revenue.